Experimental and field comparisons of two common methods for measuring microzooplankton grazing rates - Beatty, Jennifer L.; Stewart, Brittany P.; Turk-Kubo, Kendra A.; Lindell, Debbie; Caron, David A. (Frontiers in Microbiology, 2025)
IntroductionGrazing on picoplankton by microbial eukaryotes is a fundamental process within aquatic food webs, particularly in oligotrophic regions that are typically dominated by picophytoplankton. Remarkably, classical methods that have been used for decades to measure this process in the field have rarely been evaluated under controlled laboratory conditions where true rates of prey mortality can be quantified and compared to experimental results. This study evaluated two commonly used field techniques to estimate phytoplankton mortality rates by microbial consumers, the dilution technique and the disappearance of fluorescently labeled bacteria (FLB).MethodsAn elaborate laboratory experiment was first conducted comparing picophytoplankton mortality rates measured using these two techniques to rates observed directly in culture based on changes in prey abundance, using the cyanobacterium, Prochlorococcus, as prey for a nanozooplanktonic grazer, Paraphysomonas bandaiensis. Secondly, a field experiment was performed in the North Pacific Subtropical Gyre off Hawai’i to compare the mortality rates estimated by the two methods.ResultsSummed across multiple treatments in the laboratory, mortality rates estimated by FLB disappearance displayed high variability and on average underestimated observed mortality rates by ∼27%. The dilution technique also underestimated observed mortality rates (by ∼54%) but displayed lower variance (yielding an approximately 27% difference between the two methods). In contrast to laboratory results, field experiments resulted in an order of magnitude difference between grazer-mediated mortality rates using the two methods.DiscussionOur laboratory results revealed that both methods yielded reasonable albeit somewhat underestimated mortality rates in the laboratory setup, while differences between the two methods in our field studies implied that the underlying assumptions of one or both methods were not met. These findings advocate for caution in interpreting quantitative assessments of protistan-based mortality rates using these long-used approaches.